(untitled) (Islamic Sciences Journal, 2025)
This research, titled “Jurisprudential Aspects in Mulla ʿAlī al-Qārī’s Commentary on al-Shifāʾ”, is among the important studies that address selected jurisprudential issues found within one of the most significant Islamic works on the noble qualities of the Prophet (Peace Be Apon Him) namely Sharḥ al-Shifāʾ by Mulla ʿAlī al-Qārī. In this study, the researcher extracted these jurisprudential matters and presented the positions of jurists regarding them, adopting a comparative approach while remaining concise in their treatment. The research is divided into two parts: the first introduces the author and his book, and the second analyzes the jurisprudential aspects discussed therein. May Allah’s blessings and peace be upon our Master Muḥammad, his family, and his Companions.